The Preliminary Investigation into the Self-Efficacy of students taking an Accounting and Finance course in Undergraduate Engineering Degree Programmes - Gao, J.; Ward, A. E. (Elektronika ir Elektrotechnika, 2010)
An investigation into the effectiveness of teaching accounting and finance to engineering students at the University of York, England is presented. It uses data collected from students in two consecutive academic years, 2008 and 2009. The work is part of a three-year PhD research project that aims to initially establish and validate a scale measurement for self-efficacy in accounting and finance taught as part of University degree programmes. The PhD Research project then uses this measure to investigate the effectiveness of different teaching methods and student engagement activities to develop a better understanding of how educators can build self-efficacy in their student. Pre- and Post- delivery questionnaires were used to collect data for a 9-week duration course. A student identifier was used to link pre- and post- questionnaires to the same student and of the 64 completed questionnaires received, 39 (60.9%) could be matched. In addition to asking questions that would support the development of the self-efficacy scale, questions were also asked about the student’s general background, past study experience, work experience, engagement with activities (society, club or business related competition), career intention and exposure to role models. These additional questions provide the data to explore what it is the affects the students accounting and finance self-efficacy and how it develops during the course. This paper presents the background to the project, a brief review of relevant literature, the methodology and results obtained so far. It concludes with initial comments on implications for educators in this area, including a number of options for engineering educators, not only in teaching an accounting and finance course, but also in general life-long learning for engineering undergraduates.